The role of M1/M2 macrophage polarization in the pathogenesis of obesity-related kidney disease and related pathologies - Periklis Dousdampanis; Ioanna Aggeletopoulou; Ioanna Aggeletopoulou; Athanasia Mouzaki (Frontiers in Immunology)
Obesity is a rapidly growing health problem worldwide, affecting both adults and children and increasing the risk of chronic diseases such as type 2 diabetes, hypertension and cardiovascular disease (CVD). In addition, obesity is closely linked to chronic kidney disease (CKD) by either exacerbating diabetic complications or directly causing kidney damage. Obesity-related CKD is characterized by proteinuria, lipid accumulation, fibrosis and glomerulosclerosis, which can gradually impair kidney function. Among the immune cells of the innate and adaptive immune response involved in the pathogenesis of obesity-related diseases, macrophages play a crucial role in the inflammation associated with CKD. In obese individuals, macrophages enter a pro-inflammatory state known as M1 polarization, which contributes to chronic inflammation. This polarization promotes tissue damage, inflammation and fibrosis, leading to progressive loss of kidney function. In addition, macrophage-induced oxidative stress is a key feature of CKD as it also promotes cell damage and inflammation. Macrophages also contribute to insulin resistance in type 2 diabetes by releasing inflammatory molecules that impair glucose metabolism, complicating the management of diabetes in obese patients. Hypertension and atherosclerosis, which are often associated with obesity, also contribute to the progression of CKD via immune and inflammatory pathways. Macrophages influence blood pressure regulation and contribute to vascular inflammation, particularly via the renin-angiotensin system. In atherosclerosis, macrophages accumulate in arterial plaques, leading to chronic inflammation and plaque instability, which may increase the risk of CVD in CKD patients. This review focuses on the involvement of macrophages in CKD and highlights their role as a critical link between CKD and other pathologies. Targeting macrophage polarization and the ensuing macrophage-induced inflammation could be an effective therapeutic strategy for CKD and related diseases and improve outcomes for patients with obesity-related kidney disease.